The problem with temptation (2017)
"In this paper, I focus on episodes Of temptation Chat involve dynamic inconsistency. As we shall see, thesc arc cases whcrc an agent changes plans, not in response to a relevant change in her reasons, but duc to an independent change in her motivations. Dynamic inconsistency is interesting becausc it brings into close view the question whcthcr giving into temptation as such is irrational. That is, it forces us to ask whether, absent the contradiccion internal to the akratic or a problem intrinsic to the agent's judgment, giving in to temptation is in general a form of irrationality". -- Tomado de la introducción.